Internet media management system for university campus interactive tv (UTHM) - Md. Som, Mohamad (2009)
Video On Demand technology is rapidly becoming one of the most crucial tool aspects of teaching and learning for higher education. Video on demand is used by students in learning their subject matters. It help student to manage their time and place in studies style. Universiti Tun Hussein Onn Malaysia (UTHM) has initiated and decided to create his own platform of providing video-on-demand, e-learning video on demand and live telecasts via internet famously known as University Campus Interactive TV (UCiTV). UCiTV has provided numbers of streaming server to support the digital contents. The servers are categorized into video on demand and e-learning video on demand. There are also others server that located at different places which is belongs to other department and faculties. With multiple servers and multiple video on demand, it is quite difficult to manage the media in proper manner. This where a centralized management system is needs to help them to managing and indexing all the digital media into single platform. System also cans effectiveness in searching specific media from various servers within the campus.